2019
DOI: 10.3390/metabo9110264
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations and Interspecific Differences in Metabolomes of Freshwater Fish Tissues: Quantitative Metabolomic Profiles of Lenses and Gills

Abstract: This work represents the first comprehensive report on quantitative metabolomic composition of tissues of pike-perch (Sander lucioperca) and Siberian roach (Rutilus rutilus lacustris). The total of 68 most abundant metabolites are identified and quantified in the fish lenses and gills by the combination of LC-MS and NMR. It is shown that the concentrations of some compounds in the lens are much higher than that in the gills; that indicates the importance of these metabolites for the adaptation to the specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 54 publications
2
44
1
Order By: Relevance
“…The major antioxidant of the fish lens is OSH 12 . It has been shown that the level of OSH in S. lucioperca lens vary from 3 µmol/g at autumn to 1.5 µmol/g at winter 15 , which is in a good agreement with our present data ( Table 1). The concentration of the second most abundant lens antioxidant, GSH, is 3-4 times lower than that of OSH.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The major antioxidant of the fish lens is OSH 12 . It has been shown that the level of OSH in S. lucioperca lens vary from 3 µmol/g at autumn to 1.5 µmol/g at winter 15 , which is in a good agreement with our present data ( Table 1). The concentration of the second most abundant lens antioxidant, GSH, is 3-4 times lower than that of OSH.…”
Section: Discussionsupporting
confidence: 93%
“…We found in the fish tissues the following compounds with antioxidative properties: glutathione (GSH), ascorbate, OSH, and NADH. The detection of minor amounts of one more well-known thiol antioxidant, ergothioneine, in the gills of another freshwater fish, R. rutilus lacustris, has recently been reported 15 ; however, in the present work ergothioneine was not found neither by NMR nor by LC-MS in any of the studied tissues of S. lucioperca. NADH was found only in NMR spectra of liver, muscle, heart, and lens, and its concentration in these tissues does not exceed 15 nmol/g.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Metabolite enrichment analysis and pathway analysis showed the pathways establishing main differences between analyzed "experimental" groups, these including all analyses involving ovaries from Arriluze the histidine metabolism and the glutathione metabolism pathways. In a recent work by Tsentalovich et al [33], the lens-and gill-specific metabolite profiles in two freshwater fish species highlighted the histidine and glutathione metabolism pathways among the most impacted ones when comparing two different sampling seasons. The only vertebrates to present the ovoA gene in their genomes are chondrichthyans [9,15], but it has been proven that OSH-A is accumulated in some fish cells and tissues, including oocytes in salmons [1], and very importantly, the lens in different species [33,34].…”
Section: Metabolic Profile Of the Gonads Of Mussels From Arriluze Andmentioning
confidence: 99%
“…Probably, teleosts and other vertebrates accumulate OSH-A through the diet. Quantification of the levels of metabolites (combination of liquid chromatography -LC-, mass spectrometry -MS-, and nuclear magnetic resonance -NMR-) in freshwater fish lenses revealed that OSH-A it is the most important antioxidant present, and that when concentrations of OSH-A increase in autumn in comparison to winter, it occurs together with increased levels of GSH [33]. OSH-A is the result of the conjugation of cysteine and histidine, so that could be one of the drivers of the observed alterations in the histidine and cysteine metabolism pathways in mussel mantles.…”
Section: Metabolic Profile Of the Gonads Of Mussels From Arriluze Andmentioning
confidence: 99%